Mathematics Creative Thinking Skill Reviewed by Students’ Metacognitions on Creative Problem Solving Learning Model Implementation - Hardini Kurniani, Khoirida; Dwijanto, Dwijanto; Dwidayati, Nur Karomah (Journal of Primary Education, 2020)
C Creative Problem Solving (CPS) learning model supports students to focus on learning and skill processes. CPS learning, students could select, process, and develop their responses in solving a problem creatively. Metacognition plays an important role in CPS since it could monitor students in selecting and using strategy to improve further cognitive performance. This research aims to find out effectiveness of CPS learning model on mathematics creative thinking skill reviewed from students’ metacognitions. This mixed method research used sequential explanatory design. The population consisted of VIII graders at SMP N 4 Kudus. The samples consisted of experimental class with CPS learning and control class with discovery learning. The first stage of thr research was quantitative data collection. It were done using test and questionnaires to categorized the subject. The next stage was qualitative data collections which were done by using questionnaires and interview. Data of quantitative data were triangulated with the qualitative data to gain the goal of the research. The findings showed that CPS model was effective to improve creative thinking skill reviewed from students’ metacognitions. Students with high metacognition in the experimental class are more creative than the control class. CPS learning can improve students' creative thinking through the stages of idea finding to acceptance finding, because students can find new ideas and choose the right solution from some of the ideas they have. Mathematics creative thinking skill of the students with high metacognition shown form the students’ ability in writing problem solving skill of creative questions logically and could provide other notions. Students with medium category have the similar achievement but can correct errors; meanwhile students with low metacognition can wrote problem solving skill of creative questions quite logically and still have problems in giving ideas.